Food insecurity in post-crisis Sri Lanka: Evidence from the 2024-2025 BRIGHT survey - Headey, Derek D.; Stifel, Elizabeth; Hülsen, Vivien; Munasinghe, Dilusha; Ranucci, Immacolata; Sabai, Moe; van Asselt, Joanna; Weerasinghe, Krishani (International Food Policy Research Institute, 2025)
We assess food insecurity in Sri Lanka using the BRIGHT National Household Survey data for 2024-2025, which collected data on the Food Insecurity Experience Scale (FIES) developed by the FAO. • 32.8% of households in Sri Lanka experienced moderate or severe food insecurity in the 12 months prior to the survey, with 29.6% classified as moderately and 3.2% classified as severely food insecure. In contrast, food insecurity was just 12% in the 2019 Household Income and Expenditure survey (HIES), such that food insecurity has almost tripled since the 2022 economic crisis. • A very high 54.5% of Estate households (households that reside in housing on an estate/plantation) experienced food insecurity (43.2% moderate, and 11.4% severe), compared to 35.3% of urban and 31.8% of rural households. Eastern (39.1%), Uva (38.5%), and Southern (38.1%) provinces recorded the highest food insecurity rates. • Dry-zone households show slightly higher moderate and severe insecurity (34.6%) than inter-mediate (31.1%) and wet zones (24.6%). • Households dependent on informal employment are more than twice as likely to report food in-security (41% moderate, 5% severe) compared to formal employment households (18% moderate, 1% severe). • Fishing households are the most food insecure across all livelihoods with 58% experiencing moderate or severe insecurity, including 10% reporting severe food insecurity. Households de-pendent on construction (41%), agriculture (38%), textiles/artisans (35%), manufacturing (29%), food and beverage preparation (27%) and services (23%) also reported high food insecurity. • Splitting by wealth quintiles, the poorest 20% of households in Sri Lanka have a food insecurity prevalence of 45% including 10% who are severely food insecure. Food insecurity declines as wealth increases but is still high for the second (34%) and middle quintiles (25%). • The FIES-based indicator reports much higher food insecurity in 2024 (32.8%) than the WFP’s alternative CARI method of estimating food insecurity (16%). • FIES-based measures can support more frequent monitoring of food insecurity in Sri Lanka via phone surveys and help assess the impacts of programs such as Aswesuma.